2019
DOI: 10.1111/jhn.12717
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin D supplementation on muscle strength and mobility in postmenopausal women: a systematic review and meta‐analysis of randomised controlled trials

Abstract: Background The results obtained from previous trials regarding the effects of vitamin D supplementation on muscle strength and mobility in postmenopausal women have been inconsistent. This systematic review and meta‐analysis of randomised controlled trials (RCTs) aimed to investigate the effect of vitamin D supplementation on muscle strength and mobility in postmenopausal women. Methods A comprehensive search on EMBASE, PubMed, MEDLINE and SCOPUS was performed to identify relevant articles published up to 28 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…In 15 adults with thermal burns, quarterly intramuscular injections with 200,000 IU vitamin D and daily oral calcium led to a significant increase in quadriceps strength when compared to baseline values, showing a direct effect of vitamin D supplementation [ 182 ]. While a recent systematic review and meta-analysis suggested a small, non-significant ( P = 0.06) increase in muscle strength, subgroup analysis showed improvement with doses of > 1000 IU/day, > 3-month treatment duration, and in participants with a baseline vitamin D concentration of < 30 ng/mL [ 183 ]. Thus, improvements may not be seen in those individuals who have an adequate vitamin D status.…”
Section: Effects Of Covid-19 Restrictions Social Distancing and Conmentioning
confidence: 99%
“…In 15 adults with thermal burns, quarterly intramuscular injections with 200,000 IU vitamin D and daily oral calcium led to a significant increase in quadriceps strength when compared to baseline values, showing a direct effect of vitamin D supplementation [ 182 ]. While a recent systematic review and meta-analysis suggested a small, non-significant ( P = 0.06) increase in muscle strength, subgroup analysis showed improvement with doses of > 1000 IU/day, > 3-month treatment duration, and in participants with a baseline vitamin D concentration of < 30 ng/mL [ 183 ]. Thus, improvements may not be seen in those individuals who have an adequate vitamin D status.…”
Section: Effects Of Covid-19 Restrictions Social Distancing and Conmentioning
confidence: 99%
“…There is a substantial health care burden of fracture among people under 70 or without osteoporosis, suggesting that focusing on treating people with osteoporosis is unlikely to reduce a large number of fractures in the general population (61) . On the other hand, in postmenopausal women, vitamin D supplementation resulted in small but nonsignificant improvements in muscle strength compared with controls (62) . Among healthy adults, supplementation with higher doses of vitamin D (4 000 IU per day or 10 000 IU per day, compared with 400 IU per day) did not result in improved bone health; further research would be needed to determine whether it is harmful (63) .…”
Section: The Burden Of Osteoporosismentioning
confidence: 84%
“…It is not possible for us to know whether vitamin D supplementation improve hemorheology, but if it improves, probably the best supplementation protocol should be daily, to ensure a stable vitamin D level. Currently, there are many vitamin D supplementation protocols, and these protocols are usually analyzed together in systematic reviews and meta-analysis [42,43].…”
Section: Discussionmentioning
confidence: 99%